Case Report: Clinical and histopathological findings of porcelain gallbladder in a dog - Kim, Tae-Young; Oh, Ye-In (Frontiers in Veterinary Science, 2025)
Porcelain Gallbladder (PGB) is a condition marked by extensive calcification and thickening of the gallbladder wall. PGB is extremely rare in dogs. The exact mechanism of PGB remains unclear. However, chronic cholecystitis and factors such as biliary hyperplasia, mucin hypersecretion, and cystic duct obstruction can lead to fibrosis and calcification of the gallbladder wall, potentially resulting in PGB. A 13-year-old spayed female Shih Tzu presented with anorexia, lethargy, vomiting, and weight loss. Physical exams showed mild epigastric pain. Blood tests indicated mild alanine aminotransferase (ALT) elevation, significant alkaline phosphatase, and gamma-glutamyl transferase (GGT) increases. Hyperlipidemia, hypercholesterolemia, and elevated canine pancreatic lipase (cPL) were also noted. Diagnostic imaging revealed extensive gallbladder wall calcification and thickening, choleliths, mild bile duct dilation, pancreatitis, and duodenitis. Cholecystectomy was performed, and symptomatic treatment for pancreatitis and duodenitis was administered. Histopathological examination is essential for confirming PGB by identifying calcification of the gallbladder wall. Histopathological examination of the gallbladder revealed severe papillary hyperplasia, mucin hypersecretion, multiple ulcers, diffuse calcification, and fibrotic changes. These findings confirmed the diagnoses of gallbladder mucocele and PGB. Postoperatively, biochemical markers normalized or significantly decreased, with clinical improvement observed. This study presents the rare occurrence of PGB in dogs and emphasizes the importance of appropriate veterinary intervention for improving clinical outcomes.